Shades of grey: choice, control and capacity in alcohol-related brain damage - Nuala B. Kane; Norella Broderick; Emily Rao; Alex Ruck Keene; Rahul Tony Rao (BJPsych Bulletin)
Liaison psychiatrists have identified that conducting capacity assessments in general hospital patients with alcohol-related brain damage (ARBD) can be challenging. This educational article uses the fictitious case of a man with ARBD, alcohol dependence and significant self-neglect, focusing on assessment of his capacity to decide about moving into a care home on discharge. We provide an overview of clinical, legal and ethical literature relevant to decision-making and capacity assessment in individuals with ARBD, with the aim of guiding clinicians approaching complex capacity assessments.